Direct conversion of phenols into primary anilines with hydrazine catalyzed by palladium. Issue 18 (3rd April 2019) - Qiu, Zihang; Lv, Leiyang; Li, Jianbin; Li, Chen-Chen; Li, Chao-Jun
Abstract : A general and practical method to directly convert phenols into primary anilines with cheap and easy-to-handle hydrazine as the amine and hydride sources catalyzed by Pd/C. Abstract : Primary anilines are essential building blocks to synthesize various pharmaceuticals, agrochemicals, pigments, electronic materials, and others. To date, the syntheses of primary anilines mostly rely on the reduction of nitroarenes or the transition-metal-catalyzed Ullmann, Buchwald–Hartwig and Chan–Lam cross-coupling reactions with ammonia, in which non-renewable petroleum-based chemicals are typically used as feedstocks via multiple step syntheses. A long-standing scientific challenge is to synthesize various primary anilines directly from renewable sources. Herein, we report a general method to directly convert a broad range of phenols into the corresponding primary anilines with the cheap and widely available hydrazine as both amine and hydride sources with simple Pd/C as the catalyst.